Helmet Ventilation for Pediatric Patients During the COVID-19 Pandemic: A Narrative Review - Shu-Chi Mu; Shu-Chi Mu; Yu-Hsuan Chien; Yu-Hsuan Chien; Pin-Zhen Lai; Ke-Yun Chao; Ke-Yun Chao (Frontiers Media S.A., 2022)
The air dispersion of exhaled droplets from patients is currently considered a major route of coronavirus disease 2019 (COVID-19) transmission, the use of non-invasive ventilation (NIV) should be more cautiously employed during the COVID-19 pandemic. Recently, helmet ventilation has been identified as the optimal treatment for acute hypoxia respiratory failure caused by COVID-19 due to its ability to deliver NIV respiratory support with high tolerability, low air leakage, and improved seal integrity. In the present review, we provide an evidence-based overview of the use of helmet ventilation in children with respiratory failure.